Do all job changes increase wellbeing? - Cigdem Gedikli (Industrial Relations: A Journal of Economy and Society, 2025)
We provide a comprehensive framework, based on person-environment fit, for evaluating the relationship between types of job change and wellbeing, and estimate it using fixed-effects methods applied to UK longitudinal data. Changing job is associated with large swings in job satisfaction, but not all job changes are equal. Changes in workplace are associated with increased job satisfaction only when they are associated with a change in job role. The largest associations are for changing employers. These associations extend beyond job satisfaction to mental health and, to a lesser extent, life satisfaction. Changes in broader wellbeing are especially pronounced for women.